Influence of cellulose filler extracted from napier grass on thermal characterizations, moisture content, tensile strength, biodegradation, and morphological structure of bioplastic films - Rohadi, T. N.Tuan; Mohd Jamir, Mohd Ridzuan; Abdul Majid, M. S.; Mamat, Normahira; Sulaiman, M.H. (Taylor and Francis, 2022)
This paper reports on the effects of Napier grass (NG) cellulose used as a filler on the thermal characterizations, moisture content, tensile strength, biodegradation, and morphological structure of bioplastic films. Bioplastic films were obtained from chitosan and gelatin; and from the fiber, bark, and whole of Napier grass (NG). The films were prepared by solution casting with 1, 1.5, 2, and 2.5 wt.% of cellulose content. Alkali and bleaching treatments were performed on the cellulose using 8% sodium hydroxide and 1.7% sodium chlorite. The results reveal that the tensile strength of the bioplastic film with 2 wt.% of fiber filler was the highest and decreased when the cellulose filler loading was 2.5 wt.%. Increasing the cellulose loading accelerated the biodegradation rate of the bioplastic films. The addition of the fiber filler had improved compatibility among the components and the barrier properties of the film that led to a less-porous film.